Análise histopatológica do comportamento pulpar, pós cimentação de coroas totais metálicas com cimentos de ionômero vítreo e fosfato de zinco - Nogueira Junior, Lafayette [UNESP] (1997)
The purpose of this study was to conduct an histological evaluation of pulp rections of teeth after cementation of complete metal crowns with one of the following luting agents: zinc phosphate cement (ZPC) (Lee Smith, Vigodent) and two glass ionomer cements (Ketac Cem, ESPE, Vidrion C, SSWhite). Twenty seven sound bicuspids scheduled for extraction by orthodontic treatment were prepared for complete crowns, casts were made and luted with one of the above cements. Three, ten and thirty days after cementation the teeth were removed, split in two halves and the pulps detached from one of the halves, stained with H.E. and pulpal reactions assessed by optical microscopy. Results showed dissimilar inflammatory responses that were associated to the different cementing agents. For specimens of the ZPC and Ketac-Cem groups the inflammatory reaction subsided for 30 days. For the Vidrion C group only 2 out of 9 specimens showed pulpal inflammatory reactions. Therefore, regarding biocompatibility, best results were seen with the specimens ofthe Vidríon C group. The method allowed a quick assessment of pulp conditions when compared to the traditional decalcifiyng process. However, observations of dentin-pulp relationships could not be noticed